2017
DOI: 10.1634/theoncologist.2016-0331
|View full text |Cite
|
Sign up to set email alerts
|

Real-World Data on Prognostic Factors for Overall Survival in EGFR Mutation-Positive Advanced Non-Small Cell Lung Cancer Patients Treated with First-Line Gefitinib

Abstract: Background. This study aimed to identify independent prognostic factors for overall survival (OS) of patients with advanced non-small cell lung cancer (NSCLC) harboring an activating epidermal growth factor receptor (EGFR) mutation and receiving gefitinib as first-line treatment in real-world practice. Materials and Methods. We enrolled 226 patients from June 2011 to May 2013. During this period, gefitinib was the only EGFR-tyrosine kinase inhibitor reimbursed by the Bureau of National Health Insurance of Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 40 publications
(45 reference statements)
8
17
0
1
Order By: Relevance
“…Our previous report found that in the era in which only gefitinib was reimbursed by the Taiwan NHI, 33.2% of gefitinib-treated patients had M1a disease and 27.9% had brain metastasis. The median PFS of firstline gefitinib-treated patients was 11.9 months in that report, 29 shorter than the PFS in this cohort, and this supported our hypothesis. The recent prospective CTONG 0901 trial has already revealed a long median erlotinib PFS of 13.0 months.…”
Section: Discussionsupporting
confidence: 89%
“…Our previous report found that in the era in which only gefitinib was reimbursed by the Taiwan NHI, 33.2% of gefitinib-treated patients had M1a disease and 27.9% had brain metastasis. The median PFS of firstline gefitinib-treated patients was 11.9 months in that report, 29 shorter than the PFS in this cohort, and this supported our hypothesis. The recent prospective CTONG 0901 trial has already revealed a long median erlotinib PFS of 13.0 months.…”
Section: Discussionsupporting
confidence: 89%
“…Among the different sites of extracranial metastases, concomitant liver metastases were also associated with shorter OS in our analysis. This finding was consistent with the fact that liver metastases have also been observed as a predictor of poorer prognosis in a few retrospective studies despite the patients in those studies receiving different first-line treatments [26, 27].…”
Section: Discussionsupporting
confidence: 88%
“…Thus, some physicians may prefer to use erlotinib to treat BM before the use of afatinib has been validated. Nevertheless, one retrospective study found that BM at initial diagnosis had no impact on OS in EGFR mutation-positive patients treated with first-line gefitinib [26]. A subgroup analysis of the LUX-Lung 3 and LUX-Lung 6 studies disclosed that afatinib significantly improved the PFS (8.2 versus 5.4 months; HR, 0.50; p = 0.0297) and objective response rate versus chemotherapy in patients with BM [33].…”
Section: Discussionmentioning
confidence: 99%
“…5 In a real-life Taiwanese study, the observed PFS and OS were 11.9 and 26.9 months, respectively. 37 Comparable to our results, in a Californian study, TKIs had the most prominent effect on OS among all the studied treatments in stage IV nonsquamous NSCLC patients. 38 We observed certain discrepancies between IREs for OS and PFS in various studied regimens (IRE for PFS was <1 but IRE for OS was >1 for pemetrexed, bevacizumab and bevacizumab maintenance).…”
Section: Discussionsupporting
confidence: 74%